2003
DOI: 10.2202/1542-6580.1114
|View full text |Cite
|
Sign up to set email alerts
|

Digital X-ray Imaging Technique to Study the Horizontal Injection of Gas-Liquid Jets into Fluidized Beds

Abstract: Gas-liquid jets injected into fluidized beds of particles/catalyst find applications in many industrial processes. The effective distribution and mixing of the feed droplets with the entrained bed particles is vital in improving the process efficiency. The present study utilizes a sophisticated digital X-ray imaging system to study the internal flow structure of jets injected into fluidized beds. The system is equipped with an X-ray image intensifier (XRII) and optical detectors, which convert the transmitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 0 publications
6
49
0
Order By: Relevance
“…Consequently, such ''incomplete'' fluidization affect the heat and mass transfer rate in fluidized beds, and might lead to local defluidization problems [6][7][8]. Namely, the larger agglomerates tend to settle down on top of the distributor after being affected by the bed hydrodynamics [9]. These particles in the grid-zone are not much influenced by bubble motion and present the so-called ''dead zones'' between the holes of the distributor [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, such ''incomplete'' fluidization affect the heat and mass transfer rate in fluidized beds, and might lead to local defluidization problems [6][7][8]. Namely, the larger agglomerates tend to settle down on top of the distributor after being affected by the bed hydrodynamics [9]. These particles in the grid-zone are not much influenced by bubble motion and present the so-called ''dead zones'' between the holes of the distributor [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…1,3 In the case of vaporizable liquids, liquid-solid agglomerates may or may not be formed, depending on the operating conditions, 4,5 while they always form with nonvaporizable liquids. 6 Bruhns et al 7 investigated the interaction between vaporizable liquid jets and fluidized solids in a pilot-scale re-actor operated at 120-180 8C. Their study indicated that the liquid injected through commercial gas-atomization nozzles did not immediately vaporize upon direct contact with the bed solids.…”
Section: Introductionmentioning
confidence: 99%
“…With nonvaporizable liquids, using an X-ray imaging technique, Ariyapadi et al 6 visually observed the formation of liquid-solid agglomerates at the tip of the cavity formed by the liquid jet in a laboratory-scale fluidized bed of coke particles. The formation of agglomerates upon the contact between liquid jets and a small-scale fluidized bed was quantified by House et al 1,8 They injected a binder solution via gas-atomization nozzles into a fluidized bed of coke particles at room-temperature, and froze the formed agglomerates right after completing the liquid injection by interrupting the fluidization air.…”
Section: Introductionmentioning
confidence: 99%
“…In the collision model, total equilibrium cannot be attained if momentum equilibrium is achieved before total equilibrium is achieved. Table 3 Liquid jet parameters for Tests L 1 and L 3 by Ariyapadi et al (2003).…”
Section: Liquid and Solid Injection Into Dense Flow In A Channelmentioning
confidence: 99%